Effects of the exchange rate on the adoption of hedge accounting: evidence from Brasil - Sticca, Ralph Melles (2018)
Under Accounting Statement CPC 38, from 2010 on Brazilian companies started adopting accounting standards correspondent to IAS 39 regarding hedge accounting, whose disclosure is optional and, in cash flow hedge operations, may avoid losses disclosure in the income statements due to deferred values in other comprehensive income (OCI), promoting better earnings disclosure. In this scenario, by means of statistical models we investigate whether firm\'s financial exposure to currency risk and the high exchange rate depreciation environment promote the deferral of losses on firm\'s OCI and, in addition to the tax deferral on exchange gains and losses, the hedge accounting choice for 379 Brazilian listed companies between 2010- 2017. Our results show that firms\' high leverage in foreign currency, the high exchange rate variation on country level and the tax deferral choice influence positively the hedge accounting choice and, consequently, reduce the disclosure of losses on income statements, evidencing potential earnings management activity, since OCI\'s balances are not entirely understood by analysts and investors (even the most sophisticated). Our paper contributes to the disclosure, accounting choice and earnings management theories, highlighting the claim for enhancement of financial instruments accounting standards on uniformity and comparability.